1893 N.C. Sess. Laws 468-69 - (:unkn) unknown (My University, 1893)
Pub. Laws, ch. 514, §§ 1-2: Prohibiting the transfer of any pistol, pistol cartridge, brass knucks, Bowie knife, dirk, loaded cane, or slingshot to a minor.
Keywords: TRANSFER - MINORS